Post-translational modifications in sepsis-induced organ dysfunction: mechanisms and implications - Song, Lin; Jiang, Wei; Lin, Hua; Yu, Jiangquan; Liu, Ke; Zheng, Ruiqiang (Frontiers in Immunology, 2024)
As a grave and highly lethal clinical challenge, sepsis, along with its consequent multiorgan dysfunction, affects millions of people worldwide.Sepsis is a complex syndrome caused by a dysregulated host response to infection, leading to fatal organ dysfunction. An increasing body of evidence suggests that the pathogenesis of sepsis is both intricate and rapid and involves various cellular responses and signal transductions mediated by post-translational modifications (PTMs). Hence, a comprehensive understanding of the mechanisms and functions of PTMs within regulatory networks is imperative for understanding the pathological processes, diagnosis, progression, and treatment of sepsis. In this review, we provide an exhaustive and comprehensive summary of the relationship between PTMs and sepsis-induced organ dysfunction. Furthermore, we explored the potential applications of PTMs in the treatment of sepsis, offering a forward-looking perspective on the understanding of infectious diseases.